AN ANALYTICAL APPROACH TO THE NEURONAL MECHANISMS UNDERLYING THE MEMORY STORAGE IN THE BRAIN. (EXPERIMENTAL STUDY) - Koutsoukos, Elias; Angelopoulos, Elias; Maillis, Anthony; Stefanis, Costas (International Journal of Computing, 2002)
In the present in vivo experimental study, the dynamical properties of the electroencephalographic (EEG) activity recorded in the CA1 area and the dentate gyrous of rat hippocampus were investigated prior to the induction and during the maintenance phase of Long Term Potentiation (LTP). Our findings suggest that this form of brain plasticity can be reflected by the complexity of spontaneous EEG activity, as it is expressed by the reduction of the correlation dimension D2, indicates that different functional states of the brain are governed by different degrees of functional complexity.